Cultural and physiological studies on black ear mushrooms, Auricularia polytricha (Mont.) Sacc. and Auricularia auricula (L.) Underw. - r u, priya; geetha, D (Mushroom Research, 2017)
Black ear mushrooms include two cultivated species viz. Auricularia polytricha and Auricularia auricula and are widely cultivated in China. A study conducted on theÂ Cultural and physiological studies of Auricularia polytricha and Auricularia auricula indicated the superior performance ofÂ Auricularia polytricha. Among the different media tried, Carrot extract agar (8.4cm) was found to be the best followed byÂ Potato dextrose agar (6.1cm). A temperature of 200c was found to be best for the growth of both the isolates (8.5 cm). The highest mycelial growth of both Auricularia polytricha and A. auricula (8.7cm) was observed in pH 7. Artificial light conditions put up the highest mycelial growth for both the strains (8.9 cm).